Effects of different levels of dietary Citrus Limon essential oil on some blood parameters and antioxidant status in Afshari Ewes - Mojtahedin, Ali; Seifdavati, Jamal; Seyedsharifi, Reza (Cellular and Molecular Biology, 2018)
Citrus Limon Oil (CLO) is known as antioxidant resource and contains limonoids, flavonoids and phenolic compounds. This study was conducted to investigate the effects of different levels of CLO on blood parameters and antioxidant status in Afshari ewes. Six adults Afshari ewes (3-4 years old and 51±5 kg) were randomly allocated to 3í—3 Latin square design with three diets in 21 days period. Dietary treatments included:1) control diet, 2) control diet with 200 mg/day CLO, and 3) control diet with 400 mg/day CLO. To evaluate the antioxidant effect of the CLO, sustainable elimination of free radicals by DPPH and ABTS methods were used. The antioxidant activity of essential oils in DPPH method at doses of 32.5, 45, 130, 260 and 520 mg/ml were 9, 16, 31, 49 and 89%, respectively. Also, antioxidant activity of essential oils in ABTS method at doses of 32.5, 45, 130, 260 and 520 mg/ml were 49, 73, 81, 89 and 95%, respectively. CLO treatments did not affect glucose, blood urea nitrogen, albumin, total protein, low density lipoprotein, while improved the concentration of high-density lipoprotein (P>0.01). Results showed that supplementation with CLO significantly decreased (P<0.01) cholesterol, triglycerides and very low density lipoprotein concentrations compared with control. There was no significant difference in analyzed blood bio-chemicals and serum enzymes level between different antioxidant activity methods and groups, suggesting general well-being of ewes. These results suggest that, CLO supplementation had a positive impact on blood traits and antioxidant status of the Afshari ewes.